2008
DOI: 10.1007/978-3-540-78671-9_2
|View full text |Cite
|
Sign up to set email alerts
|

Winning Ant Wars: Evolving a Human-Competitive Game Strategy Using Fitnessless Selection

Abstract: Abstract.We tell the story of BrilliAnt, the winner of the Ant Wars contest organized within GECCO'2007, Genetic and Evolutionary Computation Conference. The task for the Ant Wars contestants was to evolve a controller for a virtual ant that collects food in a square toroidal grid environment in the presence of a competing ant. BrilliAnt, submitted to the contest by our team, has been evolved through competitive onepopulation coevolution using genetic programming and a novel fitnessless selection method. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
2
2

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…Various forms of CEL have been successfully applied to many two-person games, including Backgammon [10], Chess [11], Checkers [12], NERO [13], Blackjack [14], Pong [15], AntWars [16], [17] and a small version of Go [18].…”
Section: A Coevolutionary Learningmentioning
confidence: 99%
“…Various forms of CEL have been successfully applied to many two-person games, including Backgammon [10], Chess [11], Checkers [12], NERO [13], Blackjack [14], Pong [15], AntWars [16], [17] and a small version of Go [18].…”
Section: A Coevolutionary Learningmentioning
confidence: 99%
“…Despite this simplicity, it produces effective solutions and is immune to noise to an extent that is comparable to kRO (assuming the optimal value of the k parameter for kRO is known in advance). In a separate study [5], we demonstrated its ability to evolve human-competitive players in a complex game with partially observable states. The downside of the method is the extra effort required to appoint the best-of-run individual.…”
Section: Discussionmentioning
confidence: 97%
“…At present, archiving techniques are used to provide theoretical guarantees of progress in coevolutionary EAs. However, examining the genotype to phenotype map used in methods of GP which have achieved good results without archives [22] may indicate how representations inherently robust to coevolutionary pathologies can be developed.…”
Section: Conclusion and Further Workmentioning
confidence: 99%